Freies Ermessen in the Delegation of Authority from District Government to Village Government - Akhyar, Akhyar; Usman, Usman; Saifuddin, Saifuddin; Sadhana, Kridawati; Musriandi, Riki (SCAD Independent, 2023)
This study describes the problems delegating authority from the district government to the village government. The implementation of Law Number 6 in 2014 concerning villages still has shortcomings in its implementation. It is due to a lack of understanding and socialization among stakeholders who run the government in the village. This study used a qualitative approach where respondents were stakeholders in the Gampong Lamteh village, Banda Aceh. The population of this study was the village apparatus and public figures of the Lamteh Village. Thus, the total sample of this study was ten people. Data collection used observation techniques, interviews, and document analysis. The analysis of data employed the triangulation method. The study results indicated that the implementation of Law Number 6 in 2014 concerning villages are not optimal yet, where the authorities still provide a lack of socialization. There is a need for socialization to improve the stakeholders' understanding regarding authority and its restriction when performing the administration in the village.